Assessment of the Impact of the Saudi Aramco-Research Science Institute Programme in Terms of Fostering Higher-order Thinking Skills among Gifted Students at the High-school Level: تقييم أثر برنامج معهد أرامكو السعودية للأبحاث العلمية من حيث تعزيز مهارات التفكير العليا بين الطلاب الموهوبين في المرحلة الثانوية (مجلة ديالى للبحوث الانسانية, 2022)
The current study investigates the impact of the Saudi Aramco Research Science Initiative (SA-RSI) on the participating gifted and talented Saudi female students’ acquisition of higher-order thinking skills. In this investigation, a particular emphasis is placed on the students’ metacognitive skills, time-management skills, problem-solving skills and decision-making skills. This study also measures the participants’ ability to engage in metacognitive thinking in terms of planning, self-monitoring and self-assessment. A scale was applied while measuring the students’ acquisition of skills in time management, problem solving and decision-making. The researchers employed multiple training methods and strategies in order to stimulate and enhance the participants’ abilities, especially in the areas of metacognitive thinking, problem solving, decision-making and time management. The study data indicate significant pre and post differences at the level of significance of 0.01 in the participants’ mean scores pertaining to meta-cognitive thinking skills, problem-solving skills, decision-making skills and time-management skills. Section one